Chitosan Glutamate-Coated Niosomes: A Proposal for Nose-to-Brain Delivery - Federica Rinaldi; Patrizia N. Hanieh; Lik King Nicholas Chan; Livia Angeloni; Daniele Passeri; Marco Rossi; Julie Tzu-Wen Wang; Anna Imbriano; Maria Carafa; Carlotta Marianecci (MDPI AG, 2018)
The aim of this in vitro study is to prepare and characterize drug free and pentamidine loaded chitosan glutamate coated niosomes for intranasal drug delivery to reach the brain through intranasal delivery. Mucoadhesive properties and stability testing in various environments were evaluated to examine the potential of these formulations to be effective drug delivery vehicles for intranasal delivery to the brain. Samples were prepared using thin film hydration method. Changes in size and ζ-potential of coated and uncoated niosomes with and without loading of pentamidine in various conditions were assessed by dynamic light scattering (DLS), while size and morphology were also studied by atomic force microscopy (AFM). Bilayer properties and mucoadhesive behavior were investigated by fluorescence studies and DLS analyses, respectively. Changes in vesicle size and ζ-potential values were shown after addition of chitosan glutamate to niosomes, and when in contact with mucin solution. In particular, interactions with mucin were observed in both drug free and pentamidine loaded niosomes regardless of the presence of the coating. The characteristics of the proposed systems, such as pentamidine entrapment and mucin interaction, show promising results to deliver pentamidine or other possible drugs to the brain via nasal administration.